Classification of cryptocurrencies and the perception of college students about its use - Butt, Muhammad Zain (My University, 2021)
Bu çalışmanın amacı aşağıdaki soruya yanıt vermektir: Classification of cryptocurrencies and the perception of college students about its use. Araştırma üç bölüme ayrılmıştır: İlk bölüm bir giriş sağlar ve Kripto Para Birimlerinin Sınıflandırılmasını formüle eder. İkinci bölüm, kripto hakkında halihazırda mevcut olan çalışmaların bir literatür taramasıdır ve bu sistemin Avrupa'da benimsenmesinin artılarını ve eksilerini bulmaya çalışır. Devletin rolünü, yasadışı kullanımlarını ve diğer emtialarla olan bağlantılarını, merkezi olmayan yapısını, kamuyu ve değişkenliği nedeniyle oluşan güvensizliği vurgular. Üçüncü bölüm, üniversite öğrencilerinin kripto hakkında ne düşündüklerini ve bu sistemin benimsenmesini anlamak için halka açık bir ankettir. Çalışma, öğrencilerin kriptopara birimini günlük bir para biriminden daha çok bir meta olarak gördüklerine dair somut kanıtlar olduğu ve ana kullanımların hala karanlık ağda yasa dışı faaliyetler için yapılan işlemler içerdiği ve literatür incelemesinin gösterdiği gibi Avrupadaki yaklaşan yasalar ve kısıtlamalar tarafından müdahale edildiği sonucuna varıyor. Bu, aynı zamanda kripto para birimlerine yatırım yapmak isteyen yatırımcılar için fikir oluşturur.

The purpose of this study is to answer the following question “CLASSIFICATION OF CRYPTOCURRENCIES AND THE PERCEPTION OF COLLEGE STUDENTS ABOUT ITS USE” Research is divided into 3 parts. The first part provides an introduction and formulates a Classification of Cryptocurrencies according to their types. The second part is a literature review of already present studies about crypto and tries to find the pros and cons of the adoption of this system in Europe and highlights government role, its illegal uses, and links to other commodities, its decentralized nature, and public mistrust because of its volatility. The third part is a public survey from college students in order to understand what they think of crypto and its adoption of this system. The study concludes that there is factual evidence that students consider cryptocurrency as more of a commodity than an everyday currency and major uses still include transactions on the dark web for illegal activities which as shown by the literature review is being intervened by upcoming laws and restrictions in Europe. This also provides an insight for investors looking to invest in Cryptocurrencies.
Keywords: Business; Classification; Cryptocurrencies; İşletme; Students; Students Cryptocurrencies